BRAINSTORMING PELUANG BAGI LULUSAN SEKOLAH MENENGAH KEJURUAAN DI ERA REVOLUSI INDUSTRI 4.0 - yusnaidi yusnaidi; Mirdha Fahlevi; Nabila Hilmy Zhafira; Cut Mega Putri (Universitas Teuku Umar, 2022)
This community development program is implemented by the lecturers of Management Department of Teuku Umar University in collaboration with SMK Negeri 1 Meureubo. It is conducted in order to build a synergy between the world of higher education and vocational schools to improve the quality of human resources. There are three specific objectives of implementing this activity, namely; provide an understanding to vocational students about the industrial revolution 4.0, at the same time students know what skills must be prepared to be able to compete in the industrial revolution 4.0 and in the end the participants are expected to be able to share their understanding and knowledge from this activity is for their academic and social environment. This activity was attended by antusiatic students and the school authorities who really appreciated this activity because it broadened students' knowledge towards the era of the industrial revolution 4.0. This kind of activities are expected to be carried out in a sustainable manner to generate bigger impact on improving the quality of human resources for SMK graduates in West Aceh District.